2003
DOI: 10.1682/jrrd.2003.01.0009
|View full text |Cite
|
Sign up to set email alerts
|

Transverse rotation and longitudinal translation during prosthetic gait-A literature review

Abstract: Abstract-Improved technology allows for more accurate gait analysis to increase awareness of nonoptimized prosthetic gait patterns and for the manufacture of sophisticated prosthetic components to improve nonoptimized gait patterns. However, prescriptions are often based on intuition rather than rigorous research findings for evidence-based practice. The number of studies found in the literature that are based on prosthetic research regarding transverse rotation and longitudinal translation is small when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Following selection for relevance and including those resulting from the secondary search, we identified 36 articles that satisfied the criteria [2][3][5][6][7][13][14][15][16][17][18][19][20][21][22]. In addition, five relevant review articles were identified [1,[8][9][11][12]. In the following section, the approaches to characterization are considered under two broad headings: lumped parameter based methods and roll-over curve based methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following selection for relevance and including those resulting from the secondary search, we identified 36 articles that satisfied the criteria [2][3][5][6][7][13][14][15][16][17][18][19][20][21][22]. In addition, five relevant review articles were identified [1,[8][9][11][12]. In the following section, the approaches to characterization are considered under two broad headings: lumped parameter based methods and roll-over curve based methods.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, subjects preferred the prosthesis with the pylon activated. Apart from in vivo studies that compare differences in gait with and without the presence of vertical pylon compliance [12,15,[46][47][48][49][50][51], we are not aware of any studies of the effects on gait performance of changing the properties of vertical shock-absorbing pylons (AIPPs). However, a study by Coleman et al made observations on the effects of pylon bending stiffness on transtibial amputee gait [36].…”
Section: Combined In Vivo and Aipp Characterization Studies That Havementioning
confidence: 99%
See 2 more Smart Citations
“…It is claimed by manufacturers to reduce the forces acting on the residual limb during gait by simulating to a limited extent the absent kinematic functions and shock absorbing properties of the anatomical limb. These claimed advantages are clinically important, as residual limb tissue damage and joint problems, which may, at least in part, be attributable to rigid prosthetic devices, are significant problems for many lower limb amputees [1]. However, the effectiveness of this type of adapter in achieving its goals is, as yet, poorly described and this paper outlines the design of a new tool for the evaluation of the motion that occurs at the adapter during gait.…”
Section: Introductionmentioning
confidence: 99%